ANALISIS OBAT TRADISIONAL SEBAGAI MASLAHAT BAGI MASYARAKAT KONSUMTIF DALAM TINJAUAN HUKUM ISLAM (STUDI JAMINAN KEHALALAN) Desa Kaiyasa, Kecematan Oba Utara, Provinsi Maluku Utara - Riky Soleman; Sandi Mulyadi; Riswanda Imawan (Universitas KH. A. Wahab Hasbullah, 2022)
ABSTRACT Traditional medicine is a medicine from nature which is made in the form of leaves and sticks to provide a boost to the immune system. One of them is a drug that is often consumed by the community today is muscle pain medication. Because the people of kaiyasa village are getting old and vulnerable to old age, it is consumed by many people. In addition to old age, children also consume traditional medicine to maintain stamina, physical exercise and health. One of them is located in the village of kaiyasa. But in reality the community has not been able to provide new breakthroughs for traditional herbal medicines themselves, both in the scope of marketing, strategy, management to obtain certification guarantees from the halal certificate registration system to the Provincial LPPOM MUI. This study uses a quantitative approach, namely research that uses statistical analysis that focuses on hypothesis testing. This type of research was conducted to analyze traditional medicine as the benefit of the consumptive society. The results of this study indicate that based on the results of the analysis, the significance value of the user variable is 430 < Î± from 0.05 so it can be said that H0 is rejected and Ha is accepted, meaning that there is a significant effect on drug users' efficacy on the community. Based on the results of the analysis, the significance value of the behavioral variable for consuming traditional medicine is 030 < of 0.05 so it can be said that H0 is rejected and Ha is accepted, meaning that there is a significant effect on drug users' efficacy on the community.